Hepatoprotective activity of melittin on isoniazid- and rifampicin-induced liver injuries in male albino rats - Khalid Mohammed Naji; Bushra Yahya Al-Khatib; Nora Saif Al-Haj; Myrene R. D'souza (BMC, 2021)
Abstract Background The present study investigated the ameliorative effect of melittin, a major polypeptide in the venom of honeybee (Apis mellifera), on isoniazid-(INH) and rifampicin-(RIF) induced hepatotoxicity in male albino rats. Method Thirty rats (140-200 g) were divided into five groups (n = 6): normal control (NC) received normal saline orally (NaCl, 0.9%; toxic (T) group received INH + RIF (each rat received 100 mg/kg, p.o.); melittin (Mel15, Mel30) groups (each rat received 15 or 30 μg/kg s.c); and normal recovery (NR) group received INH + RIF (each rat received 100 mg/kg, p.o.). Blood and liver samples were collected for biochemical, hematological and histopathological studies respectively. Results The administration of melittin was found to prevent the antitubercular drug-induced alterations in the diagnostic markers; reduced glutathione (GSH), direct bilirubin (DB), total bilirubin (TB), aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), alkaline phosphatase (ALP), and total serum protein (TSP). Besides, hematological alterations were significantly high in Mel groups when compared to the toxic group. The NR group exhibited lower levels of DB, TB, ALP, LDH and TSP. In addition, treatment with melittin offered protection in the NR group with respect to MDA levels. Conclusion Evidence from this study suggests that melittin is beneficial for the prevention of acute hepatic failure in antitubercular drug-induced hepatoxicity and could be used as a potential therapeutic agent.